A Sensitive and Selective Liquid Chromatography/Tandem Mass Spectrometry Method for Quantitative Analysis of Efavirenz in Human Plasma - Srivastava, Praveen; Moorthy, Ganesh S.; Gross, Robert; Barrett, Jeffrey S. (PLOS ONE, 2013)
A selective and a highly sensitive method for the determination of the non-nucleoside reverse transcriptase inhibitor (NNRTI), efavirenz, in human plasma has been developed and fully validated based on high performance liquid chromatography tandem mass spectrometry (LC–MS/MS). Sample preparation involved protein precipitation followed by one to one dilution with water. The analyte, efavirenz was separated by high performance liquid chromatography and detected with tandem mass spectrometry in negative ionization mode with multiple reaction monitoring. Efavirenz and 13C6-efavirenz (Internal Standard), respectively, were detected via the following MRM transitions: m/z 314.20243.90 and m/z 320.20249.90. A gradient program was used to elute the analytes using 0.1% formic acid in water and 0.1% formic acid in acetonitrile as mobile phase solvents, at a flow-rate of 0.3 mL/min. The total run time was 5 min and the retention times for the internal standard (13C6-efavirenz) and efavirenz was approximately 2.6 min. The calibration curves showed linearity (coefficient of regression, r>0.99) over the concentration range of 1.0–2,500 ng/mL. The intraday precision based on the standard deviation of replicates of lower limit of quantification (LLOQ) was 9.24% and for quality control (QC) samples ranged from 2.41% to 6.42% and with accuracy from 112% and 100–111% for LLOQ and QC samples. The inter day precision was 12.3% and 3.03–9.18% for LLOQ and quality controls samples, and the accuracy was 108% and 95.2–108% for LLOQ and QC samples. Stability studies showed that efavirenz was stable during the expected conditions for sample preparation and storage. The lower limit of quantification for efavirenz was 1 ng/mL. The analytical method showed excellent sensitivity, precision, and accuracy. This method is robust and is being successfully applied for therapeutic drug monitoring and pharmacokinetic studies in HIV-infected patients.